Computer self-efficacy and Islamic financial literacy as determinants of Islamic accounting application adoption among sharia-based MSMEs - Irsad Andriyanto; Enny Yulianti; Marda Ulya Reksadini; Nursyuhada Ab Wahab (Journal of Islamic Accounting and Finance Research, 2026)
Purpose - This study examines the impact of computer self-efficacy and Islamic financial literacy on the intentions of Sharia-compliant MSMEs' intentions to adopt Islamic accounting programs. Method - The study employed a quantitative cross-sectional design. Purposive sampling was employed to choose respondents, and a standardized questionnaire was used to collect data from Central Java's MSME participants. The investigation was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Result - Islamic financial knowledge and computing self-efficacy both had a strong beneficial impact on adoption intention. MSME actors are more qualified to use these technologies if they believe they are more technologically literate and understand the concepts of Islamic finance. Implication - The findings highlight the importance of Islamic financial understanding and digital skill development in MSMEs' digital transformation. Originality - This study closes a gap in the literature on Islamic accounting adoption by undertaking the first empirical test of a model that integrates computer self-efficacy and Islamic financial literacy within UTAUT2 for Sharia-compliant MSMEs.